An explorative descriptive study of social and religious barriers affecting access of young black women to sexual and reproductive healthcare in Cape Town - Mlangeni, Nonhlanhla (Department of Social Development, 2026)
This explorative descriptive study used a qualitative inquiry method to explore the social and religious barriers impacting young Black women's access to sexual and reproductive healthcare in Cape Town. Previous research studies have been conducted on barriers limiting access of women to sexual and reproductive healthcare. These studies are important as women have the right to be in control of their own healthcare decisions. However, limited attention has been given to the manner in which social and religious barriers impact young Black women's access to sexual and reproductive healthcare. Fifteen participants who follows Christian norms and values were purposively sampled, and in-depth interviews were conducted to gather qualitative data. The data was thematically analysed and the process revealed various barriers affecting the access to sexual and reproductive healthcare of young Black women. The findings emphasise that access is impacted by obstacles such as a lack of communication in families, community judgment, religious doctrine, and poor attitudes from healthcare providers. The findings further highlight that schools, digital platforms and peer groups are significant channels where sexual and reproductive healthcare information can be accessed. Based on the findings of this study, recommendations include developing family communication programmes to facilitate familial discussions about female healthcare. Interventions within church settings that encourage balancing religious principles with young women's healthcare needs could also assist to address the challenges voiced by participants. Overall, this study highlights the need to protect the rights and dignity of women to access sexual and reproductive healthcare services.